Principles & Digest of the Qanun-E-Shahadat (10 of 1984) (vol. 2, Arts.70-166) - Khan, Khalil-Ur-Rehman, Justice (Lahore, Pakistan P. L. D. Publishers, 1991)
Commentary adapted from justice Monir's principles and digest of the law of evidence.
Justice Khalil-Ur-Rehman Khan, Judge, Lahore High Court.
Keywords: Evidence (Law) -- Pakistan -- Evidence (Islamic law) -- Evidence (Law)